Digital Public Service Delivery as an Institutional Outcome: Data Governance and Interoperability in The Egyptian Public Sector - Hegazy, Waad (AUC Knowledge Fountain, 2026)
Moving beyond technology-centered theories of digital transformation, this thesis examines the institutional and governance factors shaping digital public service delivery in Egypt. It analyzes how governance structures, data governance arrangements, and interoperability frameworks influence the extent to which digital transformation initiatives result in integrated, scalable, and citizen-facing public services. Using a qualitative research design, the study draws on an analysis of relevant policy and program documents and semi-structured interviews with key stakeholders involved in digital transformation initiatives in Egypt. The findings indicate that persistent challenges in digital public service delivery are driven less by technological constraints than by fragmented governance structures, ambiguous data custodianship, weak standardization, and project-based approaches to interoperability. Despite significant investments in digital platforms and service digitalization, the absence of coordinated institutional authority, incentive-aligned implementation frameworks, and consistent data standards continue to limit service integration and data exchange across government entities. The study underscores the importance of institutionalizing data governance and interoperability as foundational components of digital transformation. It concludes that digital public service delivery in Egypt should be understood as an institutional outcome contingent on effective governance arrangements, rather than as a direct product of technological adoption.